Vlogging in Digital Lesson: How it Affect EFL Students’ Speaking Skill - St. Rahmatullah; Ali Wira Rahman (La Parole : Journal of Language Teaching and Pedagogy, 2019)
This research was conducted to obtain the Perception of the use of VLOG in learning process in English Education Study Program at Universitas Muhammadiyah Parepare. This research also conducted to obtain the effects caused by VLOG as a new platform to practice speaking based on their perception. This study uses Qualitative Descriptive by design conducted with students. The population of this study is English Department of Universitas Muhammadiyah Parepare. The participant of this study consist of eight participants. In addition, the researcher conducted interview with 2 Vlogger as a proven of the effect of VLOG based on their personal experiences. The result of this study showed that VLOG is needed in language learning as a media for students to practice speaking in an interesting way. Students assumed that VLOG can help them especially in pronouncing word and decrease their anxiety. Nonetheless, it was undeniable that there are several stdents who are not suitable to use VLOG to practice speaking. Furthermore, VLOG has several advantages and disadvantages if applied in learning process.